Proposta de correlações para o módulo cisalhante e de amortecimento de solos arenosos - Barroso, Felipe Oscar Pinto (2022)
The offshore industry has been faced with occurrences of carbonate soils, which occur in tropical and intertropical zones of the planet, leading to the need to develop research on these types of soil. As a result, this research presents proposals that contribute to the prediction of the dynamic behavior of carbonate sands. Thus, two models are proposed (G/Gmax x  and D x ), using multiple linear regression and results from resonant column tests carried out in carbonate sands from Cabo Rojo (Cataño and Pando, 2010). The equations proposed for predicting the dynamic parameters of the soil, shear modulus and damping, are validated by comparing predictions made from these equations with experimental values ​​obtained by Cataño and Pando (2010). Forecasts made by these models are also compared with those of other proposals available in the literature (Hyperbolic Model (Ishihara, 1996) and Ishibashi and Zhang (1993)). The proposed equations showed agreement when compared with the values ​​observed in the laboratory by Cataño and Pando (2010). A proposal was also developed to predict the probable number of cycles (N) for the collapse by liquefaction of carbonate sands to be reached. In this stage of the study, the results obtained by Salem et al. (2013), who performed cyclic triaxial tests on sands from Dabaa, northwest Egypt. In general, predictions were obtained with moderate dispersion for the value of N, regardless of relative compactness and confining effective stress. Finally, the proposed equations were evaluated in an applied study, making predictions of the behavior of the surface foundations of a wind turbine. Frequency and amplitude predictions showed good agreement with the results obtained from parameters from seismic tests.